Recensiones - I. M. B.; S. de Anitua; Montes, Segundo; J. A. L.; L. F. V. I. (ECA: Estudios Centroamericanos, 1971)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 26, No. 270, 1971: 211-219.